Addressing COVID through PCD: policy coherence for vulnerability in development and its relationship to the coronavirus pandemic. Issue 1 (1st February 2021) - Moldes-Anaya, Sergio; Koff, Harlan; Da Porto, Angelica; Lipovina, Tara
Abstract : Purpose: The purpose of this article is to understand how coronavirus impacts relate to existing vulnerabilities in different world regions. Design/methodology/approach: The article utilizes quantitative analysis to examine regional variations in coronavirus risk assessment. It then qualitatively employs a policy coherence for development (PCD) approach to analyze how public policies contribute to or mitigate vulnerability, defined as the product of exposure to external shocks, institutional coping capabilities and risk associated with social divisions in societies. Findings: The research presented below shows that significant regional variance exists in terms of coronavirus risk, based on statistical analysis of the INFORM COVID-19 Risk Report prepared by the European Commission. The PCD analysis highlights important relationships between public policy strategies and the construction of both underlying vulnerabilities and coronavirus impacts. Practical implications: The PCD approach presented here focuses on the reconciliation of trade-offs. It shows how policy interactions affect vulnerabilities and suggests that coherent policy strategies aimed at reducing vulnerabilities are necessary in order to adequately respond to the coronavirus pandemic. Originality/value: This analysis frames vulnerability as a socially constructed condition and through implementation of a PCD approach, it indicates how policy strategies contribute to or mitigate vulnerabilities. In doing so, it intends to contribute conceptually to the literature on vulnerability by showing how policy incoherences contribute to the construction of this condition. Empirically, the originality of this article is its statistical analysis of regional variance of coronavirus risk and the qualitative analysis of policy strategies in representative cases and how they have affected vulnerabilities and coronavirus impacts.